Who Ministers to Ministers? A Study of Support Systems for Clergy and Spouses - GILBERT, Barbara G. (New York Alban Institute, 1987)
new
Keywords: CLERGY - SELF CARE; STRESS AND PASTORS; SUPPORT SYSTEMS